1988
DOI: 10.1093/oxfordjournals.humrep.a136750
|View full text |Cite
|
Sign up to set email alerts
|

The luteal phase and early pregnancy after combined GnRH-agonist/HMG treatment for superovulation in IVF or GIFT

Abstract: Endometrial biopsies showing inadequate development were observed after ovarian stimulation with the GnRH agonist Buserelin and HMG for IVF or GIFT when luteal supplementation was omitted. Ninety-one patients were randomly allocated to two luteal supplementation regimens: in 41 women HCG and in 50 women progesterone and oestradiol valerate. The pregnancy patients treated with a combination of the GnRH agonist and HMG a delay of implantation of 1.3 days was observed compared to pregnancies after clomiphene citr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(74 citation statements)
references
References 0 publications
2
67
0
5
Order By: Relevance
“…In unsuccessful cycles, the late luteal E2 levels decline which may compromise periimplantation endometrial developments [24]. Vlahose et al found that the addition of Estrogen to P in the luteal phase can increase L-selectin ligands -adhesion molecule in the endometrium during implantation [25].…”
Section: Discussionmentioning
confidence: 99%
“…In unsuccessful cycles, the late luteal E2 levels decline which may compromise periimplantation endometrial developments [24]. Vlahose et al found that the addition of Estrogen to P in the luteal phase can increase L-selectin ligands -adhesion molecule in the endometrium during implantation [25].…”
Section: Discussionmentioning
confidence: 99%
“…Through the early 1980s, GnRH1a was applied to prevent the LH surge during ovarian stimulation (9). By the end of the decade, the so-called long downregulation protocol with GnRH1a was established IVF practice, significantly reducing the rate of cycle cancellation, improving outcomes and enabling some flexibility to schedule oocyte retrieval (10). (Fig.…”
Section: Historical Perspectivementioning
confidence: 99%
“…However, some studies claim that using hCG and progesterone support increases implantation and pregnancy rates [15,16]. Smitz et al [17] first reported that in COH cycles, estradiol levels decreased in the late luteal phase and in the early gestational weeks. Parallel to this, progesterone and 17-OH-progesterone levels were also decreased.…”
Section: Discussionmentioning
confidence: 99%